Newly Defined Conformable Double Laplace Transform and Partial Differential Equations with Conformable Derivative - Labade, Meena (Communications in Mathematics and Applications, 2026)
In the present study, newly defined conformable double Laplace transform and conformable derivatives are expressed. Some new properties of conformable double Laplace transform are investigated.The efficiency and reliability of this method is illustrated by finding exact solution of initial and boundary value problems of some known fractional partial differential equations with conformable derivative.